Improved survival after resection of colorectal liver metastases in patients with unresectable lung metastases. Issue 3 (March 2020) - Albertsmeier, Markus; Riedl, Kathrin; Stephan, Anna-Janina; Drefs, Moritz; Schiergens, Tobias S.; Engel, Jutta; Angele, Martin K.; Werner, Jens; Guba, Markus
Abstract: Background: Modern systemic therapies considerably improve tumour control and thus open the possibility of new surgical approaches in metastatic colorectal cancer. In this retrospective clinical cohort with a comparison group, we investigated whether liver resection in a combined liver–lung-metastasised stage is justified if pulmonary disease is not resected. Methods: From 283 patients treated in our institution between 2000 and 2014 for combined colorectal liver- and lung metastases, 35 patients had their pulmonary metastases left in situ while they were eligible for both treatment options: resection versus non-resection of liver metastases. Effectively, 15 of these patients received whereas 20 did not receive a liver resection. In these patients, we compared overall survival and determined risk factors that are associated with poor survival, applying a Cox-Proportional Hazards model. Results: Patients whose liver metastases were resected showed significantly longer median survival compared to patients who did not undergo hepatic surgery (median 2.6 vs 1.5 years, P = 0.0182). The Cox-Proportional Hazards model revealed hepatic metastasectomy to be the strongest determinant of patient survival (HR 5.27; CI: (1.89, 14.65)). Conclusion: Our results suggest that surgical removal of liver metastases may be beneficial in selected patients even if concomitant lung metastases cannot be resected.